National survey of Japanese patients with mevalonate kinase deficiency reveals distinctive genetic and clinical characteristics. Issue 1 (2nd January 2019) - Tanaka, Takayuki; Yoshioka, Kohei; Nishikomori, Ryuta; Sakai, Hidemasa; Abe, Junya; Yamashita, Yuriko; Hiramoto, Ryugo; Morimoto, Akira; Ishii, Eiichi; Arakawa, Hirokazu; Kaneko, Utako; Ohshima, Yusei; et al.
Abstract: Objectives: Mevalonate kinase deficiency (MKD), a rare autosomal recessive autoinflammatory syndrome, is caused by disease-causing variants of the mevalonate kinase (MVK) gene. A national survey was undertaken to investigate clinical and genetic features of MKD patients in Japan. Methods: The survey identified ten patients with MKD. Clinical information and laboratory data were collected from medical records and by direct interviews with patients, their families, and their attending physicians. Genetic analysis and measurement of MVK activity and urinary excretion of mevalonic acid were performed. Results: None of the 10 patients harbored MVK disease-causing variants that are common in European patients. However, overall symptoms were in line with previous European reports. Continuous fever was observed in half of the patients. Elevated transaminase was observed in four of the 10 patients, two of whom fulfilled the diagnostic criteria for hemophagocytic lymphohistiocytosis. About half of the patients responded to temporary administration of glucocorticoids and NSAIDs; the others required biologics such as anti-IL-1 drugs. Conclusion: This is the first national survey of MKD patients in a non-European country. Although clinical symptoms were similar to those reported in Europe, the incidence of continuous fever and elevated transaminase was higher, probably due to differences in disease-causing variants.